Lost Happiness — Loss of Life Satisfaction in the Corona Crisis - Michael Ahlheim; Stefan Bruckmeyer; Kai A. Konrad; Lisa Windsteiger (Wirtschaftsdienst)
Abstract This study illustrates the loss of life satisfaction, and with it the psychological costs of the COVID-19 pandemic and the lockdown measures taken, for self-employed and women. Building on the data collected by Windsteiger et al. (2020) and their internet interviews at the peak of lockdown measures, and looking at specific population subgroups, this essay illustrates that many solo self-employed and women report a significant decline in life satisfaction, and that these effects are strongest where solo self-employment coincides with economic losses and childcare responsibilities for women with children of dependent age.